2019
DOI: 10.20517/2574-1209.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for heart failure: cell-based therapy with engineered tissue

Abstract: This review will outline cell-based therapy for heart failure focusing on tissue engineering to deliver cells to the damaged heart. We will present an overview of the central approaches focusing on pluripotent stem cell-derived cells, mechanisms of action, autologous vs. allogeneic cell approaches, immunologic modulation, and safety considerations. We will outline the progress that has been made to-date and define the areas that still need to be investigated in order to advance the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Because we are dealing with a xenograft transplant, i.e., putting human fibroblasts and human cardiomyocytes into an immune-competent rat, we studied the immune responses of the TE patch in vivo with the rats receiving no immune suppression. We showed that our TE patch partially reversed LV remodeling [18] . This work documented the therapeutic benefits of our bioengineered patch in rats with CHF.…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 64%
See 3 more Smart Citations
“…Because we are dealing with a xenograft transplant, i.e., putting human fibroblasts and human cardiomyocytes into an immune-competent rat, we studied the immune responses of the TE patch in vivo with the rats receiving no immune suppression. We showed that our TE patch partially reversed LV remodeling [18] . This work documented the therapeutic benefits of our bioengineered patch in rats with CHF.…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 64%
“…The important findings of this study were that the TE patchtreated rats decreased LV-end diastolic pressure and the time constant of LV relaxation (Tau), increased anterior wall thickness in diastole, improved echocardiographic-derived indices of diastolic function E/e' [ratio of early peak flow velocity to early peak LV velocity] and e'/a' [ratio of early to late peak LV velocity]. The graft-treated rats have a pressure/volume filling curve shifted back towards SHAM and a lower LV enddiastolic operating volume, consistent with reversal of maladaptive remodeling related to compliance [16][17][18] [Figures 2-4].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 78%
See 2 more Smart Citations
“…While management of the HF patients continues to improve, there remains a need for new therapeutic options that directly mitigate disease progression. The development of human induced pluripotent stem cells (hiPSCs) provides an opportunity to utilize novel cell types in engineered tissue platforms for regenerative therapy [ 3 , 4 ]. For the first time, hiPSC-derived cardiomyocytes (hiPSC-CMs) are being evaluated in HF patients at Osaka University, where cardiothoracic surgeons are implanting hiPSC-CM sheets on the epicardium ( NCT04696328 ).…”
Section: Introductionmentioning
confidence: 99%